Pengaruh Pelatihan Dan Lingkungan Kerja Terhadap Kinerja Kayawan Pada PT. X: The Effect of Training and Work Environment on Employee Performance at PT. X - Puja Pebria Lestari; Frida Aprillia; Fransisco Siboro (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
PT X is a company founded in 2017 as a provider of supply chain solutions for the electricity and utilities sector in Indonesia. This study aims to determine the effect of training and work environment on employee performance at PT X. The method of data collection in the preparation of this thesis is through a survey on a population of 59 people with a sample of 59 using saturated sample techniques with a quantitative analysis method. The results show that training partially has a positive and significant effect on employee performance with a significance level of 0.000 T table of 3.730> 2.003. Work Environment partially has a positive and significant effect with a level of 0.003 2.011. Training and work environment simultaneously have a positive and significant effect on employee performance with a significance level of 0.000 F table of 99.872> 3.20. These findings indicate the importance of effective training management and creating a conducive work environment to improve employee performance.